ANALISIS FAKTOR YANG MEMPENGARUHI ADOPSI RUMAH BELAJAR DI KABUPATEN KARAWANG - Diana, Larassati; Hadining, Aulia Fashanah; Fitriani, Risma (Masyarakat Telematika Dan Informasi : Jurnal Penelitian Teknologi Informasi dan Komunikasi, 2020)
Along with the development of Information and Communication Technology (ICT) had been growing more advanced. It encourages students to be technology savvy in order to make them easier in learning. One of the technology benefits in learning process is in a way of e-learning system development. The portrait of education in Indonesia in utilizing Internet, the fact showed the educational facilities and infrastructures are not well distributed to all societies, the quality of education is still low, and also the level of utilizing ICT is quite low too. The Ministry of Education and Culture which has responsibility in education developed a Learning Management System (LMS) by releasing a distance learning portal called Rumah Belajar. Rumah Belajar is an innovation that aims to improve the quality of education that allows students to study anytime and anywhere. However, Rumah Belajar is still not fully understood and accepted. This research aims to analyze the factors that influence the adoption of Rumah Belajar in Karawang. This research used five perceptions of the factors that influence the innovation adoption by using Rogers’ Diffusion of Innovation Theory such as: relative advantage, compatibility, complexity, trialability, and observability. The data were collected by distributing questionnaires to 400 respondents from high school students in Karawang. The data were analyzed by using multiple linear regression analysis. The result showed the factors that significantly influence the adoption of Rumah Belajar are compatibility, trialability, and observability. From this research, the writer hopes that all parties involved in learning process such as schools, teachers, and students have to support the utilization of Rumah Belajar.